Christian Bobin: Las ruinas del cielo - Sanz Barajas, Jorge (Razón y fe, 2018)
Edit. Sibirana, Zaragoza 2012, 134 pp., ISBN 978-84-939600-3-2 Traducción de Andrés García Inda y María José González Ordovás